PRESEPSI KARYAWAN PADA SISTEM PANEN KELAPA SAWIT DI PT.ALAM JAYA PERSADA SAMBOJA KALIMANTAN TIMUR - Pepi Herawati; Sri Ngapiyatun; Faradilla; Roby; Daryono (Politeknik Pertanian Negeri Samarinda, 2019)
The harvest system really determines the production of good fresh fruit bunches, in general the harvest system in the company uses 2 systems, namely the permanent and the sleigh design. This study aims to determine employee perceptions about the harvest system on oil palm plants. The analytical method used in this research was descriptive analysis to find out the level of knowledge of harvest employee at PT. Alam Jaya Persada. This research was conducted by using the Non Probability Sampling technique method chosen by sampling saturated (census), which is a sampling method when all members of the population are used as respondents. Based on the results of the study showed that the respondent's identity includes the gender of the harvest employees 100% are male, age between the ages of 31 to 40 years, the average education at the elementary level and the length of work at the harvest employee ranges from 1 to 9 years. Respondents' perceptions about the oil palm harvesting system, employees prefer and choose permanent design because the system is more practical and efficient and in accordance with the conditions of the plantation area.